The Middle and Upper Palaeolithic at La Crouzade cave (Gruissan, Aude, France): New excavations and a chronostratigraphic framework. (20th June 2020) - Saos, Thibaud; Grégoire, Sophie; Bahain, Jean-Jacques; Higham, Thomas; Moigne, Anne-Marie; Testu, Agnès; Boulbes, Nicolas; Bachellerie, Manon; Chevalier, Tony; Becam, Gaël; Duran, Jean-Pierre; Alladio, Alex; et al.
Abstract: This paper presents new archaeological material and first dates on Upper Pleistocene layers at the site of La Crouzade cave (Gruissan, Aude, France). The site was first excavated by T. and P. Héléna at the beginning of the twentieth century, and the excavations were recently completed during three years (2016–2018) of systematic campaigns. We obtained dates from Middle Palaeolithic layers using two methods: AMS 14 C dates were obtained from bone and charcoal, and combined ESR-U series dating was undertaken on horse teeth. Together, these methods allowed us to date this Mousterian sequence to 49, 776–44805 cal BP for the deepest level (layer C8) and from 42, 000 ± 3000 years BP for the top (layer C6). The Upper Palaeolithic layers are preserved only as patches in the actual excavation area, but a date was obtained from a piece of charcoal collected from a small hearth preserved in the first layer (C5) above Middle Palaeolithic deposits, which indicates an age similar to that of a modern human maxillary previously analysed and re-dated here from 36, 014 to 34402 cal BP, confirming its stratigraphic attribution. The Middle Palaeolithic lithics at the site were first described as para-Charentian cultural facies following typological analyses. The revision of the earlier collection supplemented with the new material, using a technological approach, allow to identify two layers dominated by Levallois production followed by discoid production (Layers C8 and C6) surrounding an original assemblage (layer C7), characterised by a dominant Levallois production completed by three secondary production systems of equal importance, including discoid, SSDA and a Quina-like production. The faunal spectrum predominantly comprises an assemblage of Pleistocene large mammals, and biochronological studies corroborate the dates obtained.